Análisis, diseño de un sistema web de control financiero, contable y tributario e implementación del módulo de facturación del Hotel Bolívar internacional de propiedad del sindicato provincial de choferes profesionales de el Oro – Machala utilizando la METODOLOGÍA SCRUM, ZEND FRAMEWORK y base de datos POSTGRESQL - Toro Matamoros, Diego José (2015)
The problem was that its processes were not automated only performed them manually which caused a number of difficulties as long as lingered in perform them, agility and ease are to be performed and one of the most important insecurity of information handles. With the above I was an urgent need to analyze, design a web system of financial, accounting and tax control, and implement the billing module using the Scrum methodology Zend framework and PostgreSQL database; the same that allows hotel managers timely information to make management decisions, helps improve control of financial processes as well as reduce the time to run accounting and tax processes, and finally allows remote access from other computers to their respective administration. For the development of system interfaces Style Sheets Cascading used in version 3, also known as CSS3, which is a language used to define the presentation of a structured document written in HTML; moreover for system validations JavaScript is a interpreted programming language was used and is mainly used on the client side, implemented as part of a web browser enabling improvements in user interface and dynamic web pages. So with the development and implementation of the system in the Hotel Bolivar International financial, accounting and tax processes significantly improved, and information processing is optimized as it is providing a flexible, easy to use and all safe; thus contributing to the institutional progress of Hotel Bolivar International owned by the provincial union of professional drivers of El Oro.